The Quran In Designing Mass Communication (Study Of Interpretation Of Al Misbah's) - Cindenia Puspasari; Muhammad Syahrial Razali Ibrahim; Danial (Faculty of Social Sciences and Humanities Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2025)
The Qur'an in designing mass communication does not only convey messages to a wide audience, but also emphasizes the values of ethical norms, truth, and justice. This article aims to deeply examine the design of mass communication from the Qur'an as interpreted in Al Misbah by M Quraish Shihab. The Al-Misbah interpretation emphasizes that the ultimate goal of mass communication design in the Qur'an is Akhlak and involves a combination of universal messages, delivery methods appropriate to the audience's context, and ethics in conveying information. This article also analyzes a pattern of prophetic communication in the Qur’an perspective that is integrated with the study of communication science that has developed previously. By referring to these principles, communication design in Islam can be relevantly applied in modern life, including through mass media. The Shannon and Weaver model is related to understanding mass communication design in the Qur'an. This article categorizes the mass communication design in the Qur'an into three models: the Story model, the Repetition model, and the Gradation model. Next, it takes four Ayahs from the Qur'an categorized into three models in the mass communication design in the Qur'an, namely: QS.An-Naml: 30, QS.Ar-Rahman: 13, QS.Al-Anbiya: 92, and QS.Al-Mu'minun: 52. Next, it is analyzed using the tahlili method based on the Al Misbah interpretation by M. Quraish Shihab. It was found that the Qur'an designs its messages broadly as a form of mass communication, aimed at achieving the ultimate intercession, which is the pleasure in understanding the meaning of the messages in the Qur'an, in order to improve human morals in leading a peaceful life